The Role of Dual-Self Constructs in Determining Payment Card Choice: Insights for Working with Credit Card Borrowers - Laura Ricaldi; Sandra J. Huston (Journal of Financial Therapy, 2019)
Evidence shows that consumers are always better off using credit cards rather than debit cards as a payment choice (King & King, 2005). This assumes that credit card payers are “convenience users” and do not carry a balance. However, we know there are habitual credit card borrowers (“revolving users”) as well as those that elect to use debit cards, even though the costs outweigh the benefits. By examining the determinants of payment choice, with a specific focus on dual-self constructs (attitudes, myopia, and financial sophistication), results from this study can provide insight for financial professionals to help mitigate the incidence of revolving credit card users. Using data from Survey of Consumer Finances (SCF) between 1998 and 2013, we find that while myopia does not explain variation between revolving credit and debit card users, there are differences in attitudes. All dual-self constructs discriminate between revolving and convenience credit card users, with attitudes having the greatest effect. Combining results from these payment choice profile comparisons suggests that financial professionals may find value in initially encouraging revolving credit card users to be debit card users, while working to change credit attitudes, with the goal of transitioning these former revolvers to convenience credit card users.